MASALAH DAN KESULITAN BELAJAR YANG DIHADAPI SISWA SEKOLAH LUAR BIASA (SLB) NEGERI SUKAMAJU ABUNG SEMULI LAMPUNG UTARA - Dewi R Wulandari; M Zainudin (Journal of Technology, Mathematics and Social Science, 2022)
Abstract: Education is a learning process in the form of positive things, education is a basic human need both physically and spiritually so that their dignity and life are more secure in the future. Children with Special Needs (ABK) are children who have abilities below or above the average of other children. In the world of education, of course, children with special needs will have difficulty in receiving and remembering information or lessons. Children with special needs are also called extraordinary children, defined as children who are different from ordinary children in terms of mental characteristics, sensory abilities, communication, social behavior, or physical characteristics. SLB is an example of an educational institution built specifically to educate and train the abilities and skills of children with special needs. This study aims to find problems and learning difficulties experienced by children with special needs in the learning process. The research was conducted at SLB Negeri Sukamaju Abung Semuli, North Lampung using the interview method. From the results of interviews conducted with one of the teachers, it was found that the problems and learning difficulties experienced by children with special needs in SLB Negeri Sukamaju Abung Semuli, North Lampung.Keywords: Children with Special Needs (ABK); Special Schools (SLB); learning problems and difficulties